Effect of drainage water recycling system management on nutrient load reduction in rice-based irrigation areas - Jie Liu; Dongguo Shao; Wenquan Gu; Yawen Liu; Zhen Wu; Chi Tang; He Wang; Jinping Feng; Jian Liu (Agricultural Water Management)
Intensive irrigation and fertilization in rice cultivation have increasingly degraded water resources and aquatic ecosystems. The drainage water recycling system (DWRS) offers a promising strategy to improve water use efficiency and reduce nitrogen (N) and phosphorus (P) losses, yet its management effects remain poorly understood. Therefore, the objective was to investigate nutrient loss dynamics and evaluate the effectiveness of DWRS management by integrating field experiments with a modified SWAT model (SWAT-DWRS), aiming to develop management strategies suitable for rice-based irrigation areas. Experimental results showed that paddy fields, ditches, and ponds each contributed to nutrient removal. However, DWRS drainage might still threaten water quality when downstream standards were stricter than Class IV. Under reduced irrigation volume and expanded pond drainage area scenarios, TN and TP loads decreased by 17.05 % and 15.44 %. These reductions were over four times greater than the reduction in runoff, indicating significant potential for water quality improvement. Higher nutrient concentrations in irrigation water enhanced nutrient removal, suggesting full utilization of aquaculture drainage for irrigation. Notably, due to interactions among paddy fields, ditches, and ponds, nutrient removal did not increase linearly with higher maximum ponding water level (Hmax), diverging from previous findings. DWRS optimization by reducing irrigation, prioritizing pond water reuse, increasing Hmax (120 mm), and expanding pond drainage area (0.44) reduced runoff, TN, and TP loads by 24.44 %, 47.91 %, and 45.52 %, respectively. These results underscore the potential of optimized DWRS management to improve water use efficiency and water quality in rice-based irrigation areas.